Understanding the reading habits and needs of Chinese-speaking senior citizens in Singapore : a case study at the Toa Payoh Public Library. - Ho, Swee Ann. (2010)
With the rapid growth of the aged population in Singapore, there is a more urgent need to help senior citizens cope with the aging process. The ideal is that they grow older with a sense of optimism and continue contributing to the society. Reading can help the silver-haired population remain mentally and socially healthy. How then can they be encouraged to read, especially those with lower literacy levels? To cater to their reading needs, it is important to know and understand their reading habits and their perspectives toward reading.